Induction of autophagy by non-structural protein 6 in important animal and human coronaviruses - Daubrah-Scott, Tyler-Josh (2025)
Coronaviruses (CoVs) are known to interfere and modulate host-cell processes to promote viral replication and evade immunity. A key role presented in available literature is that CoVs can modulate autophagy, a process critical to homeostatic maintenance. This thesis investigates the role of non-structural protein 6 (NSP6) of coronaviruses, including FCoV, the cause of feline infectious peritonitis virus (FIP), human CoV-OC43 (HCoV-OC43) and serve acute respiratory syndrome CoV 2 (SARS-CoV-2) in the manipulation of autophagy. Bioinformatic analysis, including Clustal Omega multiple sequence alignment and transmembrane prediction tools, showed that NSP6 has relatively few conserved domains and transmembrane regions across the viral species, potentially suggesting functional similarities may be preserved through structural adaptations, rather than sequence conservation.